The effect of self-foot massage on anxiety and sleep quality in nursing students: A single-blind randomized controlled study - Kezban KORAŞ SÖZEN; Songül GÜNGÖR (Universa Medicina, 2025)
BackgroundAnxiety and poor sleep quality have always caused problems for nursing students. Today, self-foot massage is considered adjunctive therapy for reducing anxiety and improving sleep quality. This study aimed to evaluate the effects of self-foot massage on anxiety levels and sleep quality among nursing students with high anxiety. MethodsAn experimental study with pre-test and post-test control groups, included 40 first-year nursing students who met the inclusion criteria (intervention= 20, control= 20). The students were randomized into intervention and control groups using block randomization. A block size of four was employed to maintain equal group sizes. State Anxiety Inventory (SAI) and Pittsburgh Sleep Quality Index (PSQI) were used to collect the data.  In the self-foot massage group, subjects attended foot massage sessions at the same time every day for 10 days. Independent t-test and  Chi-square method was used to analyze the data. ResultsThe intervention group performing self-foot massage demonstrated significantly lower mean scores for PSQI (7.70 ± 1.5) and SAI (34.10 ± 4.82) compared to the control group, whose mean scores were 8.00 ± 2.65 and 38.80 ± 3.04, respectively (p=0.03; p=0.021). These differences indicate improved sleep quality and reduced anxiety in the intervention group. Subjective sleep quality was also found to be better among participants in the intervention group. However, no significant differences were observed between the groups in the PSQI subcomponents (p>0.05). ConclusionSelf-foot massage can be considered as a potential therapeutic intervention that improves sleep quality and reduces anxiety among nursing students with high level anxiety.